Implementing the One Day One Verse Method to Increase Motivation to Memorize the Quran - Sondang Sondang; Deni Zein Tarsidi; Joko Daryanto (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This research is motivated by the inconsistency of the tahfidz supervising teacher in using the teaching method or method, namely still using the deposit system. In this system, students often continue to the next verse even though they have not completely memorized the previous verse. This causes some students to experience difficulties when depositing memorization, such as stumbling in reading, skipping some verses, and not being correct in using tajwid or makharijul huruf. The purpose of this study is to determine: (1) the application of the One Day One Verse (ODOA) method in increasing motivation to memorize the Qur'an, (2) increasing motivation of students in memorizing surahs (3) supporting and inhibiting factors in the application of the One Day One Verse method. This type of research is field research with a qualitative approach. The research subjects include tahfidz supervising teachers, management teachers, students, and parents of students. The data collection techniques used consist of observation, interviews, and documentation. Data analysis is carried out through three stages, namely data reduction, data presentation, and drawing conclusions. Based on the research and discussion, it was found that the ODOA method was applied to students who had already memorized the Quran fluently. Once they had memorized the Quran fluently, the supervising teacher targeted one new verse by dictating each verse fragment to be memorized. Furthermore, the supervising teacher used keywords in each verse and provided tajweed rhythms to help the students memorize the verses and improve their tajweed accuracy.